Multilevel analysis of determinants of polygyny among married men in Ethiopia - Yitayish Damtie; Bereket Kefale; Melaku Yalew; Mastewal Arefaynie; Bezawit Adane (BMC, 2021)
Abstract Background Polygyny occurs when a man has more than one wife at the same time. It often contributes to poor health among family members, particularly young children. It encourages the spread of sexually transmitted infections (STIs) including HIV/AIDS. The determinants of polygyny have not yet been adequately explored in Ethiopia. This study adds to the body of knowledge concerning the prevalence and distribution of polygyny in the country. Methods This study is a secondary analysis of the 2016 Ethiopian Demographic and Health Survey (EDHS) data. Using a two-stage stratified cluster sampling, 7470 married men were selected. After verifying the assumptions of multilevel logistic regression analysis, Stata version 14.0 was used to analyse the data. A multilevel mixed-effects logistic regression model was used to identify predictors of polygyny. An adjusted odds ratio with a 95% confidence interval was used to measure the association. A p-value of < 0.05 was considered to indicate statistical significance. Results Age from 30 to 44 years [AOR = 5.78, 95% CI = (3.13, 10.7)], age from 45 to 59 years [AOR = 16.5, 95% CI = (8.59, 31.8)], men with primary education or no formal education [AOR = 3.40, 95% CI = (1.50, 7.69)], being Muslim [AOR = 2.47, 95% CI = (1.28, 4.77)], sexual initiation at or above the age of 18 years [AOR = 0.46, 95% CI = (0.30, 0.68)] and being from a less developed region of Ethiopia [AOR = 3.67, 95% CI = (2.30, 5.83)] were factors associated with polygyny. Conclusion Both individual and community level factors were identified as predictors of polygyny. Improving educational attainment and delaying men's sexual debut could encourage the reduction of polygyny in Ethiopia.